Responses in Zinc Uptake of Different Mycorrhizal and Non-mycorrhizal Crops to Varied Levels of Phosphorus and Zinc Applications - Yu, Bao-Gang; Chen, Xiu-Xiu; Cao, Wen-Qing; Liu, Yu-Min; Zou, Chun-Qin (Frontiers in Plant Science, 2020)
Negative effects of high phosphorus (P) application on zinc (Zn) nutrition have been observed in many crops. This study investigated the Zn responses of three typical crops to varied P and Zn applications. A pot experiment was conducted using two mycorrhizal crops (maize and soybean) and one non-mycorrhizal crop (oilseed rape) under three levels of P, two levels of Zn, and two levels of benomyl. Results showed that P application significantly decreased shoot and root Zn concentrations, Zn uptake, and Zn acquisition efficiency (ZnAE) of the three crops irrespective of Zn rate, and that these reductions were greater for maize and soybean than for oilseed rape. Zn application alleviated the P inhibition of Zn uptake in the three crops. The arbuscular mycorrhizal fungi (AMF) colonization of maize and soybean contributed most to the negative effects of increasing P application on Zn uptake, explaining 79–89 and 64–69% of the effect, respectively. For oilseed rape, root dry weight and root Zn concentration explained 90% of the decrease in Zn uptake caused by P application. These results suggest that there is another pathway in addition to the mycorrhizal pathway regulating Zn uptake under mediation by P supply.